POSITION OF PERSONAL GUARANTEE ASSET SEIZURE IN BANKRUPTCY PRINCIPAL DEBTOR - Sidauruk, Jupenris; Sunarmi, Sunarmi; Aflah, Aflah (NOMOI Law Review, 2025)
General Seizure of Personal Guarantee Assets in the Bankruptcy of the Principal Debtor, can be carried out and regulated in the provisions of the Bankruptcy Law and Civil Law. So that the Personal Guarantee has responsibility for the bankruptcy statement of the principal debtor, but in practice there is an interesting phenomenon, for example, in the Medan District Court Decision Number 6/Pdt. Sus-Others/2019/PN. Niaga. Mdn. there is a phenomenon of the seizure of Personal guarantee assets without a bankruptcy statement against the Personal Guarantee. Normative legal research with a statutory regulatory approach and case studies. The results of this study indicate that Article 1832 of the Civil Code number 2 states that the position between the Principal Debtor and the Guarantor or Personal Guarantee or Borgtocht is the same as a Debtor. Personal Guarantee assets cannot be seized in the bankruptcy of the Principal Debtor, a sign that there is a bankruptcy statement against the Personal Guarantee and the Personal Guarantee releases its Special Rights. In Decision Number: 6/Pdt. Sus-Lain-lain/2019/PN. Niaga. Mdn Jo. Number: 2/Pdt. Sus. Bankrupt/2018/PN. Niaga does not reflect justice, therefore the Personal Guarantee assets are not included in the Bankrupt Boedel because the Personal Guarantee is not bankrupt, so that general seizure cannot be carried out and general seizure is not in accordance with the contents of the guarantee agreement that has been agreed upon by the creditor and guarantor.